WEST actively cooled load resilient ion cyclotron resonance heating system results. (12th August 2021) - Hillairet, J.; Mollard, P.; Colas, L.; Helou, W.; Urbanczyk, G.; Bernard, J.-M.; Delaplanche, J.-M.; Durand, F.; Faure, N.; Garibaldi, P.; Lombard, G.; Bourdelle, C.; et al.
Abstract: Three identical new WEST ion cyclotron resonance heating (ICRH) antennas have been designed, assembled then commissioned on plasma from 2013 to 2019. The WEST ICRH system is both load-resilient and compatible with long-pulse operations. The three antennas have been successfully operated together on plasma in 2019 and 2020, with up to 5.8 MW of coupled power. The load resilience capability has been demonstrated and the antenna feedback controls for phase and matching have been developed. The breakdown detection systems have been validated and successfully protected the antennas. The use of ICRH in combination with lower hybrid has triggered the first high confinement mode transitions identified on WEST.